PERBEDAAN PENDAMPINGAN SUAMI DAN METODE TAPPING TERHADAP PENURUNAN TINGKAT KECEMASAN DAN INTENSITAS NYERI PADA PERSALINAN NORMAL - Munjiati Munjiati; Dina Indrati DS; Herry Prasetyo (Bhamada: Jurnal Ilmu dan Teknologi Kesehatan (E-Journal), 2016)
Background: husband mentoring and methods tapping in the intra-partum period can be used as an alternative methods during delivery Purpose: the study aimed to determine the effect husband mentoring and methods tapping the intra-partum period to decrease the level of anxiety and pain intensity in normal labor. Method: the research method was quasi experiment with non equivalent control group pre test and post test. The population was mothers with normal deliveries in the maternity hospital in the field of Community Health Center Baturaden Banyumas. The sample size was 30 women. Data collection was done before and after assisting with the tapping method, using observation sheet measurement of anxiety and pain intensity scale. Results: the findings showed that there are significant differences in mean anxiety and pain in the first stage of intrapartum before and after the intervention period in the intervention group, with a very strong correlation values are 0.853 and 0.764. The average value of the significance of anxiety level in the intervention group was 0.000 < 0.05 and the average value of the significance of reduction in pain intensity was 0.001 < 0.05. Meanwhile, the control group, the level of significance 0.005 < 0.05 for an average of anxiety before and after counseling, but not to a category average of childbirth pain first stage is 0.635 <0.05. Conclusion: tapping method assistance is very meaningful to reduce pain and anxiety in the mother gave birth to the first stage of intrapartum